2003
DOI: 10.1007/s00125-003-1037-4
|View full text |Cite
|
Sign up to set email alerts
|

A dominant negative PPARγ mutant shows altered cofactor recruitment and inhibits adipogenesis in 3T3-L1 cells

Abstract: Aims/hypothesis. PPARγ, a member of the nuclear hormone receptor family of transcription factors, plays a key role in adipocyte differentiation and insulin sensitivity. The aim of this study was to identify a potential dominant negative murine PPARγ mutant and to characterize the in vitro functional properties of this mutant. Methods. In vitro transient transfections and mammalian two-hybrid assays in TSA201 cells were used to characterize the transcriptional activity of the L466A mutant and to study the molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
46
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 69 publications
6
46
0
Order By: Relevance
“…1C). The PPAR␥ L466A mutant has no inherent transcriptional activity (22). The lack of homozygote viability is consistent with the embryonic death seen in homozygous PPAR␥ null animals (9).…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…1C). The PPAR␥ L466A mutant has no inherent transcriptional activity (22). The lack of homozygote viability is consistent with the embryonic death seen in homozygous PPAR␥ null animals (9).…”
Section: Resultssupporting
confidence: 66%
“…This behavior is analogous to the properties of dominant negative thyroid receptor ␤ mutants associated with the syndrome of resistance to thyroid hormone (31). We have previously shown that the L466A mutation studied here exerts stronger dominant negative activity than the P465L mouse mutant (P467L in humans) (22). In contrast to the L466A mutant (PPARKI), a P465L dominant negative PPAR␥ knock-in mouse model does not exhibit features of the metabolic syndrome (32).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The expression vector pCMX-mPPAR␥ contains the fulllength PPAR␥ complementary DNA under the cytomegalovirus (CMV) promoter in the pCMX vector. Dominant-negative PPAR␥ mutant L466A was generated by polymerase chain reaction-based site-directed mutagenesis (obtained from Dr. J. Larry Jameson, Northwestern University Medical School, Chicago, IL) (33). Dominant-negative PPAR␥ (L468A/ E471A) was constructed by mutation of 2 highly conserved residues in the ligand-binding domain (obtained from Dr. Krishna K. Chatterjee, University of Cambridge, Cambridge, UK) (34).…”
Section: Methodsmentioning
confidence: 99%